On the edge of history: small political parties & groupings in South Africa’s transition, 1990-1997 - Robinson, J (2016)
Much of the academic - and popular - literature on the South African negotiations process focuses on the two principal players, the African National Congress (ANC) and the National Party Government. A significant number of other political groupings were vying for influence at this time and although they would not fare well electorally in 1994, their influence and also their symbolic importance has been overlooked. Four groupings that have found themselves on the margins of the South African transition are the subject of this thesis: The white right wing (Afrikaner Volksunie, the Conservative Party, the Freedom Front); the homelands (in particular Bophuthatswana, KwaZulu and Transkei), the Democratic Party (DP) and the Pan Africanist Congress (PAC). All four of these political groupings were deeply involved in the transition process and critically, offered very different options and scenarios for the future. These included alternative visions of a federal South African state, a more independent judiciary, stronger provincial powers and greater degrees of cultural and territorial self-determination. For some of the parties - notably the PAC- the compromises reached in the constitution around property rights were unacceptable. In the case of the PAC, Inkatha and some far-right Afrikaner groupings, there was a turn to violence - even if not always sanctioned by leadership - that had an important impact on conditioning the settlement. The differing trajectories and prescriptions of these groupings offer up important lessons regarding the history of the negotiations period, the potential for alternative pathways during this time as well as the deficiencies of the current constitutional order. The histories of these marginal groupings on the sidelines of a historic settlement speak to longstanding fault lines in South Africa’s political discourse, including the role and salience of liberalism, socialism and ethno-nationalism in the post-apartheid era.